Effect of Distributed Versus Massed Practice on Reaction Time in Collegiate Volleyball Players: A Pilot Study - Kiran Negi (JCDR Research and Publications Private Limited, 2021)
Introduction: Reaction Time (RT) is the time taken by an individual to respond to external stimuli. It is one of the most important determinant ability in sports like Volleyball. Shorter RT leads to higher performance and success in Volleyball. Two types of training methods, massed and distributed practice have been used in researches to improve RT and other sports related skills in sports. In massed practice, there is persistent workout with hardly any rest periods even of minimal time period relative to the work interval while in distributed practice; it is interspersed with rest or other skill learning. There are mixed evidences on effectiveness of these practice methods which has led to the present study. Aim: To find the effect of distributed practice and massed practice in terms of RT among collegiate volleyball players. Materials and Methods: The study design was quasi-experimental pilot study that was conducted at the volleyball academy Gurugram, Haryana, India from September 2019 to December 2019. A total of 30 players, aged 18-22 years, from college volleyball team were invited to participate in the study. Subjects were randomly divided into two groups. Group A received massed practice (n=15), and group B received distributed practice (n=15) for 40 minutes, four days a week for four weeks. Players who were practicing daily for one hour were included in this study and they were excluded if they had any condition that limited their participation in the study or if they are suffering from any type of orthopaedic or neurological illness. RT was measured using Ruler Drop Test (RDT) and Red Light Green Light Test (RLGL). Data was analysed using Statistical Package for the Social Sciences (SPSS) version 20.0 for statistical analysis. Results: The mean pre and post data of Group A, for RDT was 0.16 and 0.12 seconds, respectively; of Group B, it was 0.16 and 0.13. The mean pre and post data of Group A for RLGL was 0.42 and 0.38 seconds, respectively; Group B data for RLGL pre and post was 0.39 and 0.37 seconds, respectively. Both the groups showed significant improvement in scores of RDT (p-value for Group A=0.01, Group B=0.05) and RLGL (p-value for Group A=0.01, Group B=0.01) measured by the paired sample t-test (p<0.05). But there was no significant difference in between group analysis measured by independent sample t-test (p>0.05). Conclusion: This study showed that both massed and distributed practice was helpful in improving RT of collegiate volleyball players. As there was no significant difference between the two groups, consequently which practice method is superior in improving RT in collegiate volleyball players could not be stated.